Choosing patient-reported outcome measures for cancer clinical research – Practical principles and an algorithm to assist non-specialist researchers - Luckett, T.; King, M.T. (European Journal of Cancer, 2010)
Abstract: Aim: The purpose of this article is to give practical advice to researchers wishing to choose measures of quality of life and other patient-reported outcomes (PROs) for cancer clinical research. Method: Readers are guided through the process of selecting a patient-reported outcome measure (PROM) by means of six principles, illustrated with examples. Results: PROM selection should always be undertaken with consideration of specific objectives, samples, treatments and available resources. Guiding principles include: (1) always consider PROMs early in the design process within the context of other methodological decisions; (2) choose a primary PROM that is as proximal to the cancer and/or its treatment as will add to knowledge and inform practice; (3) identify candidate PROMs primarily on the grounds of scaling and content; (4) appraise the reliability, validity and ‘track records’ of candidate PROMs in studies similar to that planned; (5) look ahead to practical concerns; and (6) take a minimalist approach to ad hoc items. Conclusion: The principles and algorithms presented in this article will assist cancer clinical researchers who lack specialist expertise in patient-reported outcome measurement to make appropriate choices when selecting PROMs for their next study.